2023
DOI: 10.3390/biomedicines11030767
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification Model for Severe COVID-19 Disease: A Retrospective Cohort Study

Abstract: Background: Risk stratification models have been developed to identify patients that are at a higher risk of COVID-19 infection and severe illness. Objectives To develop and implement a scoring tool to identify COVID-19 patients that are at risk for severe illness during the Omicron wave. Methods: This is a retrospective cohort study that was conducted in Israel’s second-largest healthcare maintenance organization. All patients with a new episode of COVID-19 between 26 November 2021 and 18 January 2022 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The study population included all MHS members with a positive SARS-COV-2 PCR or reported antigen test (carried out by MHS or Ministry of Health (MOH)) from March 2020 (first case in Israel) until the beginning of July 2022 (end of study period). In MHS, most of the COVID-19 patients were followed up by either a centralized, bespoke, online service [4] or by their family physicians, on the basis of an organizational scoring system of corona-risk severity [19]. The study population was then divided into two groups: those who were treated in the Post-COVID-19 clinic and those who were not.…”
Section: Methodsmentioning
confidence: 99%
“…The study population included all MHS members with a positive SARS-COV-2 PCR or reported antigen test (carried out by MHS or Ministry of Health (MOH)) from March 2020 (first case in Israel) until the beginning of July 2022 (end of study period). In MHS, most of the COVID-19 patients were followed up by either a centralized, bespoke, online service [4] or by their family physicians, on the basis of an organizational scoring system of corona-risk severity [19]. The study population was then divided into two groups: those who were treated in the Post-COVID-19 clinic and those who were not.…”
Section: Methodsmentioning
confidence: 99%
“…One positive example would be the use of risk stratification models to identify patients that are at a higher risk of COVID-19 infection and severe illness [25]. These models have made possible the prioritization of patients requiring closer follow-up by their physicians and outreach services, as well as identifying those that are most likely to benefit from anti-viral treatment during the fifth wave of infection in Israel, dominated by the Omicron variant [26]. Precision public health by using more accurate measures of disease spread, susceptibility, and behavior to assess population health and develop targeted programs can also support broader COVID-19-related public health efforts [27].…”
Section: Aligning Precision Medicine With Evidence-based Medicine: Is...mentioning
confidence: 99%
“…This autumn booster was offered to the Dutch population aged 12 years and older, and targeted especially clinically vulnerable individuals (medical risk group) and individuals aged 60 years and older (3). People with a medical risk and elderly people are at higher risk of developing severe disease after SARS-CoV-2 infection (4) and a high vaccination uptake in this group is thought to be essential to avoid excess morbidity and mortality (5,6,7).…”
Section: Introductionmentioning
confidence: 99%